Biochemical and inflammatory parameters in intensive care unit and nonintensive care unit COVID-19 patients – A retrospective study - Muragendraswami N Astagimath; Raviraja Aryapu; Suman Doddamani (Apollo Medicine)
Background: COVID-19 presents with varied clinical presentations. Most of the patients have a good prognosis, but some patients rapidly progress to severe disease. Hence, early identification of severity becomes important. Aims and Objectives: This study aimed to compare the ferritin, troponin I, and D-dimer in intensive care unit (ICU) (severe) and non-ICU (nonsevere) patients of COVID-19. Materials and Methods: Data were collected from COVID-19 laboratory (n = approximately 2700). The patients were divided into ICU and non-ICU group. Ferritin and troponin I were estimated by chemiluminescence immunoassay and D-dimer was estimated by turbidimetric immunoassay. Results: Troponin I levels were comparable between the groups. Ferritin was elevated (P = 0.0001) in ICU patients compared to non-ICU patients. The levels of D-dimer were increased (P < 0.0001) in the ICU group compared to the non-ICU group. Conclusion: Despite the fact that troponin I may not be a decent indicator for the seriousness of the infection, it might be of use in patients with cardiovascular risk factors. Raised levels of ferritin might be a significant marker that demonstrates the chance of requiring escalated care for the COVID-19 patients. D-dimer can be used as a judicious marker for suggesting the severity and prognosis of the disease.